2012
DOI: 10.1186/1477-7819-10-61
|View full text |Cite
|
Sign up to set email alerts
|

Single-port laparoscopic colectomy versus conventional laparoscopic colectomy for colon cancer: a comparison of surgical results

Abstract: BackgroundSingle-port laparoscopic surgery is a new technique that leaves no visible scar. This new technique has generated strong interest among surgeons worldwide. However, single-port laparoscopic colon surgery has not yet been standardized. Our aim in this study was to evaluate the feasibility of single-port laparoscopic colectomy compared with conventional laparoscopic colectomy for colon cancer.MethodsWe conducted a case-matched, controlled study comparing single-port laparoscopic colectomy to convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…The literature search identified one randomized contro lled trial and 13 cased-matched control or comparative studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . In total, 1559 colorectal resections were included, 589 by SILC and 970 by CLC.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified one randomized contro lled trial and 13 cased-matched control or comparative studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . In total, 1559 colorectal resections were included, 589 by SILC and 970 by CLC.…”
Section: Resultsmentioning
confidence: 99%
“…A cohort study of 73 patients by McNally et al 14 in 2011 concluded that SILC can be used safely in selected colon cancer patients with no difference in blood loss, operating room time, or lymph node retrieval. A similar study by Egi et al 15 comparing surgical outcomes for colon cancer showed no significant differences regarding the perioperative and oncologic results between SILC and MLC. The only reported advantage of SILC was the better cosmetic outcome.…”
Section: Silc For Malignancymentioning
confidence: 60%
“…The only reported advantage of SILC was the better cosmetic outcome. 15 There is only 1 randomized controlled trial in the literature comparing SILC and MLC for colonic neoplasms. 16 In this study, Poon et al 16 selected patients with small cancers (Ͻ4 cm) or adenomatous polyps requiring colectomy and randomized them to undergo either SILC or MLC.…”
Section: Silc For Malignancymentioning
confidence: 99%
“…We believe the contributing factors for this request are that patients feel safer in the hospital and daily bed costs are low. Mean length of hospital stay varies between 4 to 10 days in some studies (1,3,7,8). Park et al (4) compared this technique with conventional laparoscopic colorectal surgery (C-LCS) and found that blood loss, resection margin length, and morbidity were similar but the operation time in single port surgeries were shorter.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal procedures with this method have also begun during the same period. According to results from studies on single incision surgical procedures, this method has a slight advantage over conventional laparoscopic procedures with less pain, less length of hospital stay and faster recovery (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%